Integrated Transcriptional Regulatory Network of Quorum Sensing, Replication Control, and SOS Response in Dinoroseobacter shibae - Koppenhöfer, Sonja; Wang, Hui; Scharfe, Maren; Kaever, Volkhard; Wagner-Döbler, Irene; Tomasch, Jürgen (Frontiers in Microbiology, 2019)
Quorum sensing (QS) coordinates population wide gene expression of bacterial species. Highly adaptive traits like gene transfer agents (GTA), morphological heterogeneity, type 4 secretion systems (T4SS), and flagella are QS controlled in Dinoroseobacter shibae, a Roseobacter model organism. Its QS regulatory network is integrated with the CtrA phosphorelay that controls cell division in alphaproteobacteria. To elucidate the network topology, we analysed the transcriptional response of the QS-negative D. shibae strain ∆luxI1 towards externally added autoinducer (AI) over a time period of 3 hours. The signalling cascade is initiated by the CtrA phosphorelay, followed by the QS genes and other target genes, including the second messenger c-di-GMP, competence, flagella and pili. Identification of transcription factor binding sites in promoters of QS induced genes revealed the integration of QS, CtrA phosphorelay and the SOS stress response mediated by LexA. The concentration of regulatory genes located close to the origin or terminus of replication suggests that gene regulation and replication are tightly coupled. Indeed, AI first stimulates and then represses replication. The restart of replication comes along with increased c-di-GMP levels. We propose a model in which QS induces replication followed by differentiation into GTA producing and non-producing cells. CtrA-activity is controlled by the c-di-GMP level, allowing some of the daughter cells to replicate again. The size of the GTA producing subpopulation is tightly controlled by QS via the AI Synthase LuxI2. Finally, induction of the SOS response allows for integration of GTA DNA into the host chromosome.